Citizenship Learning Strategies Based on Local Values: A Qualitative Study in Elementary Schools - Rahmawati, Febriana Nur; Assingkily, Rizki (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2024)
Civic education at the elementary school level often encounters challenges in internalizing citizenship values in a contextual and meaningful manner. This study aims to explore strategies for teaching civic education based on local values and their impact on students’ understanding and civic attitudes. Employing a qualitative approach with a case study design, data were collected through observation, in-depth interviews, and documentation at a primary school in Kendari City. Data analysis was conducted using NVivo software to identify key emerging themes from field findings. The results reveal that the integration of local values—such as cooperation (gotong royong), deliberation (musyawarah), and social concern—into instructional strategies enhances student participation, fosters civic character, and strengthens the connection between learning materials and students’ sociocultural realities. These findings offer significant implications for the development of contextual curricula and character education rooted in local wisdom. This strategy is considered effective in cultivating inclusive, participatory, and culturally grounded civic understanding from an early age.